ANALISIS PENGARUH PERPUTARAN MODAL KERJA TERHADAP TINGKAT PROFITABILITAS (STUDI KASUS PADA PERUSAHAAN SUB SEKTOR HOTEL DAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013) - B51111067, Vivi Batista (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
All companies have a principal purpose of improving the welfare of the shareholders. One of the ways of achieving the objective is to increase the company’s profitability. The entire resources of the company should be utilized optimally to gain profitability. Working capital constitutes one of the important factors that can have a direct impact on the company’s profits. The more efficient the working capital is used by the company, the higher the profitability will be achieved. This research aimed to find out the influence of working capital turnover on profitability in the hotel and tourism companies listed on the Indonesia Stock Exchange. The population in this research consisted of hotel and tourism companies listed on the Indonesia Stock Exchange amounting to 11 companies in the period of 2011-2013. The data analysis technique was the simple linear regression analysis technique which was used to test or predict the influence of one independent variable on the dependent variabel with the SPSS computer program. The results showed that 1) the working capital turnover (WCT) had a negative influence on profitability (ROE); 2) working capital turnover measured by WCT had no significant influence on the level of profitability measured by ROI; 3) working capital turnover (WCT) had a negative influence on profitability (EP); and 4) working capital turnover (WCT) had a positive influence on profitability (TATO). Keywords : IDX, working capital turnover, profitability.